Additive Manufacturing of Ankle-Foot Orthosis with Predefined Ankle Stiffness—A Case Report. Issue 4 (October 2020) - Vasiliauskaite, Egle; Van Paepegem, Wim; Deckers, Jan Patrick; Vermandel, Miguel; Forward, Malcolm; Plasschaert, Frank
ABSTRACT: Introduction: The success of orthotic interventions depends on how well an individual patient's needs are identified and addressed. In this prospective study, we addressed the following question: Is it possible to additively manufacture an ankle-foot orthosis (AFO) with predefined ankle stiffness that would decrease excessive plantarflexion in the dropfoot gait? Materials and Methods: A child with unilateral drop foot was recruited for this study and took part in three gait assessments. In the first gait assessment, the "optimal" AFO stiffness was determined using a hinged AFO with adjustable ankle stiffness. A leaf-spring-type AFO with predefined optimal ankle stiffness was then virtually designed and additively manufactured. The impact of this orthosis on the patient's gait before and after 6 weeks of acclimatization period was evaluated in the second and the third gait assessments, respectively. Results: A hinged orthosis with an ankle stiffness of 0.009 N·m·deg −1 ·kg −1 was deemed to be the optimal for the study patient. The ankle stiffness of the additively manufactured AFO was 0.008 N·m·deg −1 ·kg −1 . This orthosis decreased patient's excessive plantarflexion, but its impact was moderately inferior compared with that of the optimal hinged orthosis. Conclusions: Despite having the same ankle stiffness, hinged AFO and leaf-spring AFO did not produce the same gait pattern. Therefore, to prescribe an optimal AFO, a better understanding of subject-AFO interaction in walking is needed.